Fluoride-Controlled Riboswitch-Based Dampening of Gene Expression for Cloning Potent Promoters - Korniakova, Vesta; Devinck, Aurélie; Groleau, Marie-Christine; Déziel, Eric; Perreault, Jonathan (Frontiers in Genetics, 2022)
Bioreporter systems based on detectable enzyme activity, such as that of beta-galactosidase or luciferase, are key in novel bacterial promoter discovery and study. While these systems permit quantification of gene expression, their use is limited by the toxicity of the expressed reporter enzymes in a given host. Indeed, the most potent promoters may be overlooked if their activity causes a lethal overproduction of the reporter genes when screening for transcriptional activity of potential promoter sequences with the luxCDABE cassette. To overcome this limitation, a variation of the mini-CTX-lux plasmid has been designed which allows reduction of promoter activity via the addition of an adjacent fluoride riboswitch. The riboswitch adds a layer of regulation between the promoter and the reporter gene, allowing cloning of stronger promoters by weakening expression, while still providing a good signal for weaker promoters by inducing with fluoride, thus circumventing limitations associated with reporter toxicity. We noticed some unexpected behavior of the riboswitch in terms of portability between species, suggesting caution when using riboswitches non-native to the species where it is being used. This study introduces a new molecular biology tool which will allow for the identification of previously unverifiable or uncharacterized potent promoters and also provides a cloning vector for translational fusion with luciferase in a plasmid compatible with many species such as from the genera Burkholderia and Pseudomonas.